Funkcje łączące - podstawowe pojęcia i własności - Heilpern, Stanisław (Copulas - basic notions and properties, 2006)
The paper is devoted to the copulas, which are the important tools for studing the dependence between random variables. The basic definitions, notions, theorems and properties connected with copulas are presented. The main families of copulas: Archimedean and elliptical are investigated. The frailty model strictly connected with Archimedean copulas and relations between the copulas and the coefficients of correlations: Kendall’s, Spearman’s, Pearson’s and tail dependence are studied. The last section is devoted to the methods of simulation from copulas. The simulation of the distribution of sums of random variables is presented.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1105, s. 27-52